An Application of Crystal Plasticity to predict Forming Limit Curve of Dual-Phase Steels with Validation - Venkata Kiranmayi Abburi; Uppaluri Rohith; Pilthammar Johan; Gutkin Renaud (MATEC Web of Conferences)
In this paper an alternative approach for generating Forming Limit Curve (FLC) of a Dual-Phase (DP800) steel is presented and validated. Investigation was performed using a rate-dependent crystal plasticity (CP) framework solved through a spectral solver and combined subsequently with the Marciniak-Kuczynski (M-K) approach for the evaluation of FLC using the commercial software Digimat. Representative Volume Element (RVE) was constructed using the built-in Voronoi tessellation method within Digimat from the Electron Back Scattering Diffraction (EBSD) measurements on the material. The hardening parameters were calibrated through inverse optimisation to match the experimental uniaxial tensile behaviour of the material. The calibrated model was then used as a virtual testing tool to predict the anisotropic yield behaviour of the DP800 steel and the Yld2000 function was fitted to the predicted anisotropic yield surface. The fitted Yld2000 function was then used to determine the FLC using the M-K approach implemented in Digimat where the sheet necking is modelled through an initial imperfection as a narrow band with reduced thickness. The whole workflow was successfully validated with experimental evaluation of FLC. The results are satisfactory and demonstrate the suitability of the presented workflow for FLC evaluation of advanced steels.